Risk Factors of Anencephaly: A Case Report - Hamka Koerslo; Nicko Pisceski (Indonesian Journal of Global Health Research, 2025)
This case report discusses the risk factors of anencephaly, a severe neural tube defect characterized by the absence of brain tissue and the skull. The study highlights the role of maternal obesity and folic acid deficiency as contributing factors. A 22-year-old woman (G3P0A2H0) at 26-27 weeks of gestation was diagnosed with an anencephalic fetus during an ultrasound examination, showing the ‘frog face’ sign. The patient had a history of two spontaneous abortions, a BMI of 30.4, and no folic acid supplementation. Pregnancy termination was planned and conducted using misoprostol, resulting in the delivery of a stillborn male fetus weighing 1500 g, with Apgar Score 0/0. The findings emphasize the importance of early folic acid supplementation and weight management in preventing neural tube defects. Pregnancy termination remains a viable option due to the poor prognosis associated with anencephaly.